2017
DOI: 10.3892/ol.2017.6891
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant chromatin remodeling in gynecological cancer (Review)

Abstract: Abstract. Epigenetic regulatory mechanisms are a current focus in studies investigating cancer. Chromatin remodeling alters chromatin structure and regulates gene expression, and aberrant chromatin remodeling is involved in carcinogenesis. AT-rich interactive domain-containing protein 1A (ARID1A) and SWItch/sucrose non-fermentable-related, matrix-associated, actin-dependent regulator of chromatin, subfamily a, member 4 are remodeling factors that are mutated in numerous types of cancer. In gynecological cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…1 illustrates the effects of the loss of ARID1A expression and its impact on carcinogenesis, although the precise mechanisms that triggers cancer development have not yet been fully elucidated. ARID1A expression disorders disrupt the function of SWI/SNF and the chromatin remodeling mechanism, causing epigenetic abnormalities in gene expression with severe consequent effects in the cell identity and possible carcinogenicity (41,(84)(85)(86). In addition, functional studies of ARID1A have demonstrated that its tumour-suppressive action lies both in the control of cellular proliferation and in maintaining the integrity of the genetic material, which is why both roles of guardian and caretaker of the genome are attributed to it (3,13).…”
Section: Abnormal Epigenetic Regulation Of Arid1a Expressionmentioning
confidence: 99%
“…1 illustrates the effects of the loss of ARID1A expression and its impact on carcinogenesis, although the precise mechanisms that triggers cancer development have not yet been fully elucidated. ARID1A expression disorders disrupt the function of SWI/SNF and the chromatin remodeling mechanism, causing epigenetic abnormalities in gene expression with severe consequent effects in the cell identity and possible carcinogenicity (41,(84)(85)(86). In addition, functional studies of ARID1A have demonstrated that its tumour-suppressive action lies both in the control of cellular proliferation and in maintaining the integrity of the genetic material, which is why both roles of guardian and caretaker of the genome are attributed to it (3,13).…”
Section: Abnormal Epigenetic Regulation Of Arid1a Expressionmentioning
confidence: 99%
“…In addition, somatic mutations private to either the SBT or HGSC were identified; the SBT harboured a CDKN2A hotspot mutation, and the HGSC showed SMARCA4 and CREBBP loss‐of‐function mutations coupled with LOH, as well as EP300 and MYCL1 missense mutations (Figure ). Of note, SETD2 , EP300 and SMARCA4 are chromatin‐remodelling genes, aberrations in which play an important role in carcinogenesis . These data suggest that, although the SBT and HGSC of case 2 are clonally related, parallel evolution took place and the lesions acquired private driver alterations.…”
Section: Resultsmentioning
confidence: 88%
“…Ovarian tumours that commonly show alterations in chromatin‐remodelling genes include clear cell and endometrioid carcinomas, and small cell carcinomas of hypercalcaemic type . Alterations in several genes involved in chromatin remodelling have also been reported in serous carcinomas, more commonly in those arising in the endometrium (including CHD4 , EP300 , ARID1A , FBXW7 , and SPOP ) than in those arising in the adnexa . The Cancer Genome Atlas (TCGA) analyses identified SMARCA4 alterations in a minority of ovarian HGSCs, a small subset of which lacked identifiable TP53 mutations .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The loss of PR expression and functionality in endometrial cancer cells could stimulate MYC the expression of MYC [196]. In addition to an imbalance in the levels of ER/PR signaling and their effector nuclear receptor (NR) coregulators [197], the development of endometrial cancer is also regulated by the DNA repair activity of DNA mismatch repair (MMR) pathways, silencing/ mutations in tumor suppressors, and dysregulation of the chromatin remodeling pathways [198,199,200,201]. In general, a reduction in the level of MMT repair activity combined with growth promoting ER’s genomic- and -nongenomic signaling events might also contribute to growth stimulation.…”
Section: Endometrial Cancermentioning
confidence: 99%